Enhancing critical reading skills through summarizing and paraphrasing strategies to improve comprehension and analytical thinking in learners - Pande Putu Resmia Ovieta; I Nyoman Suka Sanjaya; Zulfiqar Ali; Sadia Ayub; Dr. Mahmood Eshreteh (Yayasan Mitra Persada Nusantara, 2026)
This study aims to investigate the effectiveness of summarizing and paraphrasing techniques in enhancing reading skills, particularly focusing on developing critical reading abilities. The research employs a mixed-methods approach involving a quasi-experimental design complemented by qualitative analysis. Participants included high school students divided into experimental and control groups; the experimental group received targeted instruction in summarizing and paraphrasing strategies within the context of critical reading exercises. Data were collected through pre- and post-tests assessing reading comprehension and critical thinking, alongside observation and interviews to gain insights into students’ engagement and strategy application. The analysis revealed that students trained in summarizing and paraphrasing demonstrated significant improvement in identifying main ideas, synthesizing information, and evaluating textual arguments compared to the control group. Qualitative findings underscored enhanced metacognitive awareness and deeper engagement with texts when students actively practiced these strategies. The results support the hypothesis that integrating summarizing and paraphrasing into critical reading instruction promotes not only comprehension but also analytical skills essential for academic success. In conclusion, this study highlights the pedagogical value of explicit instruction in summarizing and paraphrasing to cultivate critical reading competencies. It recommends incorporating these strategies systematically in reading curricula to foster higher-order thinking and empower students to become independent, reflective readers.